Causes and Patterns of Tooth Extraction among the Patients Attending a Dental Hospital in Peshawar, Pakistan - Ilyas, Muhammad; Kundi, Jawad Ahmad; Khan, Sara; ., Ambreen; Amin, Sumaira; Shah, Tehmina (Journal of Gandhara Medical and Dental Science, 2016)
OBJECTIVE The aim of this study was to determine the primary reasons for tooth extraction and the type of tooth involved in extraction. METHODOLOGY A cross-sectional study was conducted after the approval of the ethical committee of the hospital at the Department of Oral and Maxillofacial Surgery, Sardar Begum Dental Hospital from July 2015 to December 2015. A total of n=4230 permanent tooth extractions were included with female n=2532 and male n=1698. The primary reasons for tooth extraction specified were caries, periodontal diseases, prosthetic and orthodontic purposes, impaction and trauma. The data was analyzed using SPSS-22. Descriptive statistics was applied for causes and frequency of tooth extraction. Chi-square tests were performed using p ≤0.05 significance level to determine if any significant difference existed among the genders. RESULTS The mean age presentation was 39.6±15.9 years and the age range 13-70 years. The female patient predominate n=2532 (59.85%) the male patients n=1698 (40.12%). Caries was the dominant cause of extraction in both subjects n=2652 (62.70%), followed by periodontal disease n=930 (22.00%), prosthetic purpose n=366 (8.70%), orthodontic purpose n=156 (3.70%) while cause of extraction due to trauma n=30 (0.70%) was the least one in both subjects. In female the dominant arch is mandibular arch n=1404 (55.45%) than maxillary arch n=1128 (44.55%) while in male maxillary arch n=906(53.36%) predominate the mandibular arch n=792 (46.64%). First permanent molars n=936(11.07% ) were the most common tooth type involved in tooth extraction in both genders [upper: n=408 (9.64%), lower: n=528 (12.50%)]. Upper central incisor n=120 (2.84%) is the least common tooth involved in tooth extraction. The chi-square test illustrates that there is no significant difference exist among both subjects (chi-square=0.9797, p=0.323). CONCLUSION Caries is the dominant cause of extraction and the most frequent teeth involved in extraction is lower first molar.